Strategic decision-making in the chaos-era - Prorok, V.; Švihlíková, I. (Ye.A.Buketov Karaganda State University Publ., 2014)
The society meets many challenges in the form of interlinked and complicated problems. Experts using different methodological schools and of various ideological or religious directions try to find solutions to them. One of possible options is the systemic approach and its latest elaboration — the chaos theory, which works with non-linear systems, one of which is society. This article proposes to make strategic decisions in globalization era one possible alternative — the theory of Kondratieff cycles, which fits into the theory of chaos and allows authors to analyze specific events in the past 50 years and predict the possible risks of future development.
Хаос заманындағы стратегиялық шешімдерді қабылдау
Принятие стратегических решений в эпоху хаоса
Keywords: Methodology; Systems approach; Chaos Theory; Kondratiev‘s cycles; Political control; Globalization